2020
DOI: 10.1038/s41598-020-72587-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effects of virtual reality training and sensory motor training on bone morphogenic proteins and inflammatory biomarkers in post-traumatic osteoarthritis

Abstract: The objective of this study is to compare the effects of virtual reality training (VRT) and sensory-motor training (SMT) in bone morphogenetic proteins (BMP) and inflammatory biomarkers expression in post-traumatic osteoarthritis (PTOA) after the anterior cruciate ligament injury. Through a simple random sampling method, 60 eligible participants were allocated into VRT (n = 20), SMT (n = 20), and control groups (n = 20). They underwent training programs for 4 weeks. Clinical (pain intensity and functional disa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…Numerous studies have previously reported an association between CSP and changes in inflammatory cytokines, such as IL-1 and TNF-α, which are thought to be closely related to the pathogenesis of disc herniation and degeneration [ 64 , 65 ]. Similarly, Nambi et al [ 66 ] reported that 4 weeks of VR training could significantly decrease pain intensity, increase functional impairment, and improve CRP, TNF-α, IL-2, IL-4, and IL-6 levels. However, the limited number and low quality of the included studies need to be noted, and further RCTs with large samples and rigorous study designs are needed to elucidate these results.…”
Section: Discussionmentioning
confidence: 98%
“…Numerous studies have previously reported an association between CSP and changes in inflammatory cytokines, such as IL-1 and TNF-α, which are thought to be closely related to the pathogenesis of disc herniation and degeneration [ 64 , 65 ]. Similarly, Nambi et al [ 66 ] reported that 4 weeks of VR training could significantly decrease pain intensity, increase functional impairment, and improve CRP, TNF-α, IL-2, IL-4, and IL-6 levels. However, the limited number and low quality of the included studies need to be noted, and further RCTs with large samples and rigorous study designs are needed to elucidate these results.…”
Section: Discussionmentioning
confidence: 98%
“…In patients with mid-stage KOA (K-L grade 3), joint space narrowing, significant cartilage damage, increased functional impairment, and intensified pain are observed. Most of the studies we included (Abdelazeem et al, 2016;Nambi et al, 2020;Mete and Sari, 2022;Ozlu et al, 2023;Oliveira et al, 2024)…”
Section: Effects Of Vr-based Exercise On Different K-l Grades Of Koamentioning
confidence: 99%
“…No significant differences regarding limb loading, balance, ROM, and functional tests were found [26]. A VR training protocol has shown beneficial improvement compared to sensory-motor training in post-traumatic knee osteoarthritis (KOA) after ACL injury, concerning not only pain and function but also inflammatory biomarkers without effect on bone morphogenic proteins [27]. Two RCTs using VR training after total knee replacement (TKR) showed no superiority over conventional rehabilitation regarding improvement of outcomes with a possible better effect on global proprioception [28,29].…”
Section: Complex Regional Pain Syndrome (Crps)mentioning
confidence: 99%